Cataract Prevalence and Its Associated Factors among Adult People Aged 40 Years and above in South Ari District, Southern Ethiopia - Temesgen Wolde Kentayiso; Agune Ashole Alto; Zeleke Abebaw; Direslgne Misker; Wanzahun Godana Boynito (Advances in Public Health)
Background. Cataract is the leading cause of blindness in Ethiopia. However, the treatment was only surgery; the expected person could not use the surgical service. So far, the World Health Organization’s goal of 2,000 people using the treatment out of a million people could not be met. Objective. The aim of this study was to assess the prevalence of cataract and factors associated with among adult people aged 40 years and above in South Ari district of South Omo Zone, Ethiopia. Method. A community-based cross sectional study was conducted in South Ari district of South Omo Zone, Ethiopia; samples were selected using simple random sampling and eye examination. Data were collected using pretested structured questionnaires. Data quality was ensured by daily supervision completeness and consistency. The data were coded, entered, and cleaned by using Epi.info version 7 and were analyzed by using SPSS version 20. Bivariate and multivariable analysis was carried by binary logistic regression. Significances were declared by using a p value of <0.05 and AOR of confidence intervals. Result. In this study, the prevalence of cataract was found to be 7.8% (95% CI: 5.0–10.6). There is an increased chance of developing cataract among females (AOR 3.52; 95% CI: 1.39–8.83), individuals with known history of hypertension (AOR 4.5; 95% CI 1.56–13.21), adults aged 70–79 years (AOR 5.07 95% CI: 1.09–23.62), and adults aged 80 years and above (AOR 6.01; 95% CI: 1.29–27.92). Conclusions. Cataract prevalence was found to be high among the study participants. Age, sex, and known history of hypertension were factors associated with cataract.